Mali : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Nonobservance of Performance Criteria, and Deletion and Modification of Performance Criteria-Staff Report; Staff Statement; Press Release; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report ;, 2008)
This paper presents Mali's First Review under the Poverty Reduction and Growth Facility, and requests for Waiver of Nonobservance of Performance Criteria. The food and fuel price shocks have begun to moderate, partly because of the authorities' supply-side measures and declining oil prices. New risks are emerging from the global credit crisis and its spillover effects onto global growth, commodity markets, and exchange rates. The authorities need to be vigilant on the fiscal front because policies have relaxed owing to external food and fuel price shocks and higher-than-expected nondebt financing.